NATURAL BIOPOLYMER-BASED COMPOSITES: PROPERTIES AND PROSPECTS OF UTILIZATION IN CONSTRUCTING TRANSDERMAL FORMULATION OF VACCINES - M. N. Kireev; O. A. Volokh; A. K. Nikiforov (Разработка и регистрация лекарственных средств, 2019)
Represented are the results of model experiments in the construction of chemical plague-vaccine transdermal variant prototype. Objective of the study is to demonstrate the possibility in principle to design natural biopolymer-based composite and feasibility of its application as depot antigens of chemical vaccines by the example of plague microbe capsular antigen.